2012
DOI: 10.2298/vsp1205425b
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin and BISAP score versus c-reactive protein and APACHE II score in early assessment of severity and outcome of acute pancreatitis

Abstract: In early assessment of AP severity, PCT has better predictive value than CRP, and similar to the APACHE II score. APACHE II score is a stronger predictor of the disease severity than BISAP score. PCT is a good predictor of AP outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 43 publications
(41 reference statements)
2
9
0
Order By: Relevance
“…Most of the patients have mild disease with minimal morbidity, and the rest of the patients have 10%-20% of mortality in SAP [6]. In this study based on MCSI, there were 69 (42%) SAP patients who are similar to Bezmarevic et al study [7]. Cho et al in their study of 161 AP patients reported that 52 patients with SAP had APACHE II score ≥8 similar to this study [8].…”
Section: Discussionsupporting
confidence: 68%
“…Most of the patients have mild disease with minimal morbidity, and the rest of the patients have 10%-20% of mortality in SAP [6]. In this study based on MCSI, there were 69 (42%) SAP patients who are similar to Bezmarevic et al study [7]. Cho et al in their study of 161 AP patients reported that 52 patients with SAP had APACHE II score ≥8 similar to this study [8].…”
Section: Discussionsupporting
confidence: 68%
“…Ten studies were excluded due to insufficient data to calculate the effect estimates, leaving thirteen studies included into the qualitative synthesis. Further, two records were excluded as they studied SAP defined by the 1992 Atlanta classification [ 18 , 19 ]. Two studies investigated the same cohort [ 20 , 21 ], and the study with more comprehensive data was selected [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…The pooled sensitivity and specificity values were 64.82 and 83.62%, respectively, from the meta-analysis of the diagnostic performance of the BISAP in 1,972 individuals from 9 research studies [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ], indicating a good specificity but moderate sensitivity in diagnosing SAP. These sensitivity and specificity values confirmed the findings of several other studies that the BISAP score was a reliable and accurate means for predicting the severity of AP in the early phase [ 10 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of these 18 articles, 9 were excluded: 4 non-English language articles, 3 reviews and 2 studies without sufficient data for calculations. Finally, 9 studies [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ] that involved 1,972 subjects were included in the meta-analysis.…”
Section: Methodsmentioning
confidence: 99%